Event-Related Desynchronization and Corticomuscular Coherence Observed During Volitional Swallow by Electroencephalography Recordings in Humans - Koganemaru, Satoko; Mizuno, Fumiya; Takahashi, Toshimitsu; Takemura, Yuu; Irisawa, Hiroshi; Matsuhashi, Masao; Mima, Tatsuya; Mizushima, Takashi; Kansaku, Kenji (Frontiers in Human Neuroscience, 2021)
Swallow in humans involves many cortical areas although it is partly mediated by a series of brainstem reflexes. Cortical motor commands are sent to muscles during swallow. Previous studies using magnetoencephalography showed event-related desynchronization (ERD) during swallow and corticomuscular coherence (CMC) during tongue movements in the bilateral sensorimotor and motor-related areas. However, there have been few analogous studies using electroencephalography (EEG). We investigated the ERD and CMC in the bilateral sensorimotor, premotor and inferior prefrontal areas during volitional swallow by EEG recordings in 18 healthy human subjects. As a result, we found a significant ERD in the beta frequency band and CMC in the theta, alpha, and beta frequency bands during swallow in those cortical areas. These results suggest that EEG can detect the desynchronized activity and oscillatory interaction between the cortex and pharyngeal muscles in the bilateral sensorimotor, premotor and inferior prefrontal areas during volitional swallow in humans.